Most Common Bacterial Growth in Inflamed Gallbladder Bile Post Cholecystectomy in Mosul, Iraq - Khalid, Omar R.; Ali, Ali J.; Almoula, Jasim M. J. (Scientific Journal of Medical Research, 2021)
Objective: To elucidate the most common bacterial growth in bile perioperatively in patients with cholecystitis, and the pattern of antibiotic sensitivity, to detect the most appropriate antibiotic treatment. Patients and Methods: A prospective case series study, from july 2020 to may 2021, consisted of 98 patients were diagnosed with cholecystitis by clinical judgment, ultrasound, intraoperative finding and histopathological examination. accordingly the patients was divided into 2 groups, group A (acute cholecystitis) 44 (45%) cases, and group B (chronic cholecystitis) 54 (55%) cases, bile samples were aspirated from gallbladder post operatively, and sent for bacteriological examination in sterile container, and then directly inoculated onto various bacterial media (blood agar, mackonky agar and tetrathionate broth). laproscopic cholecystectomy was done in 85 cases, while 13 cases undergone open cholecystectomy. 8 cases were opened from the start, and only 5 cases were difficult and so converted to open surgery later. Results: Among 98 patients, bile culture was positive in 63 (64.2%) samples. 41(93%) samples were positive in acute cholecystitis, while only 22 (40.7%) were positive in chronic cholecystitis. Ninety two (93.8%) cases were calculus cholecystitis, and only 6 (6.2%) cases were acalculus cholecystitis. 62 (68%) cases of calculus cholecystitiswere culture positive, and only 1(17%) case of acalculus cholecystitis were culture positive. The most common microorganism isolated in both acute and chronic cholecystitis was Escherichia coli, it was 28 (68.3%) in acute cholecystitis and 16 (72.7%) in chronic chlecystitis, the second microorganism isolated was Klebsiella pneumoniae, it was 6 (14.6%) in acute cholecystitis and 3 (13.7%) in chronic cholecystitis, the third microorganism was Staphylococcus aureus. It was 3 (7.3%) in acute cholecystitis and 1 (4.5%) in chronic cholecystitis. The fourth microorganism was salmonella, 2 (4.8%) in acute cholecystitis and 1 (4.5%) in chronic cholecystitis. Pseudomonas aeruginosa also was 2 (4.8%) in acute cholecystitis, and 1 (4.5%) in chronic cholecystitis. There was no significant statistical difference between both types of infection regarding types of bacteria. There was no significant statistical difference in the distribution of bacteria according to gender. Bacterial sensitivity was (96%) to imipenem, and (88%) to cefepem, (87%) to levofloxacin, (80%) to amikacin, (73%) to gentamycin and (68%) to ciprofloxacin. Bacterial sensitivity to second and third-generation cephalosporins was negative in all samples. Conclusion: most common isolated organism were gram-negative rods such as E. coli, and Klebsiella, followed by S. aureus. The bile of patients with cholecystitis is infected with bacteria in more than (64%) of cases, with a higher incidence in acute cholecystitis. Most microorganisms were sensitive to imipenem and fourth-generation cephalosporine (cefepem), And resistant to second and third-generation cephalosporins.